Adaptive Manufacturing for Healthcare During the COVID-19 Emergency and Beyond - Vallatos, Antoine; Maguire, James M.; Pilavakis, Nikolas; Cerniauskas, Gabrielis; Sturtivant, Alexander; Speakman, Alexander J.; Gourlay, Steve; Inglis, Scott; McCall, Graham; Davie, Andrew; Boyd, Mike; Tavares, Adriana A. S.; et al. (Frontiers in Medical Technology, 2021)
During the COVID-19 pandemic, global health services have faced unprecedented demands. Many key workers in health and social care have experienced crippling shortages of personal protective equipment, and clinical engineers in hospitals have been severely stretched due to insufficient supplies of medical devices and equipment. Many engineers who normally work in other sectors have been redeployed to address the crisis, and they have rapidly improvised solutions to some of the challenges that emerged, using a combination of low-tech and cutting-edge methods. Much publicity has been given to efforts to design new ventilator systems and the production of 3D-printed face shields, but many other devices and systems have been developed or explored. This paper presents a description of efforts to reverse engineer or redesign critical parts, specifically a manifold for an anaesthesia station, a leak port, plasticware for COVID-19 testing, and a syringe pump lock box. The insights obtained from these projects were used to develop a product lifecycle management system based on Aras Innovator, which could with further work be deployed to facilitate future rapid response manufacturing of bespoke hardware for healthcare. The lessons learned could inform plans to exploit distributed manufacturing to secure back-up supply chains for future emergency situations. If applied generally, the concept of distributed manufacturing could give rise to ‘21st century cottage industries’ or ‘nanofactories’, where high-tech goods are produced locally in small batches.